A Case of Histiocytic Sarcoma Arising from Mycosis Fungoides - Burns, Ethan A. (Case Rep Hematol, 2019)
Histiocytic sarcoma (HS) is an uncommon malignant neoplasm arising from mature histiocytes and most commonly characterized by the immunophenotypic expression of CD68, CD163, or lysozyme. Although rare, HS arising as a second primary malignancy following hematolymphoid neoplasms has been reported. To our knowledge, this is the first reported case of HS occurring as a second primary malignancy in a patient with mycosis fungoides (MF), with the retained immunophenotype markers CD30 and CD4.